2015
DOI: 10.1093/femsle/fnv195
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of doxycycline against vesicular stomatitis virusin vitro

Abstract: Doxycycline (Dox) is a tetracycline derivative with broad-spectrum antimicrobial activities that is used as an effector substance in inducible gene-expression systems. We investigated the antiviral activity of Dox against vesicular stomatitis virus (VSV) infection in cultured H1299 cells. Dox at concentrations of 1.0-2.0 μg ml(-1) significantly inhibited VSV replication and the VSV-induced cytopathic effect in dose-dependent manners, suggesting that Dox may have broader activity in inhibiting viral replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
3
39
1
Order By: Relevance
“…This hypothesis was confirmed by in vitro experiments demonstrating that the effect of DOX was directed more toward viral entry than toward viral replication [169]. Furthermore, the inhibitory effect of DOX on the replication of vesicular stomatitis virus (VSV) in different stably infected cell lines was reported [170]. The results showed significant inhibition of the replication of VSV in a dose-dependent but not cell-type dependent manner, suggesting that DOX exerted its antiviral activity at the early-mid stage of VSV infection [170].…”
Section: Doxycyclinementioning
confidence: 77%
See 3 more Smart Citations
“…This hypothesis was confirmed by in vitro experiments demonstrating that the effect of DOX was directed more toward viral entry than toward viral replication [169]. Furthermore, the inhibitory effect of DOX on the replication of vesicular stomatitis virus (VSV) in different stably infected cell lines was reported [170]. The results showed significant inhibition of the replication of VSV in a dose-dependent but not cell-type dependent manner, suggesting that DOX exerted its antiviral activity at the early-mid stage of VSV infection [170].…”
Section: Doxycyclinementioning
confidence: 77%
“…It has been reported that these therapies could have activities beyond antimalarial activity, also against viral infectious agents. Surprisingly, in many cases, the administration of antibiotics alone or in combination with other antiviral agents showed significant antiviral activities against different types of viral infections [168][169][170][171]. Despite this evidence, the antiviral mechanisms of action have not been completely investigated.…”
Section: Antimicrobial Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve-well plates were seeded with BHK-21 cells and cultured overnight. 10 μM PGG was added at various stages of the virus infection [ 38 ]: 1 or 2 h before RABV infection (−2, −1 h p.i. ), together with RABV infection (0 h p.i.…”
Section: Methodsmentioning
confidence: 99%